Stable Isotope Techniques for the Assessment of Host and Microbiota Response During Gastrointestinal Dysfunction. Issue 1 (January 2017) - Butler, Ross N.; Kosek, Margaret; Krebs, Nancy F.; Loechl, Cornelia U.; Loy, Alexander; Owino, Victor O.; Zimmermann, Michael B.; Morrison, Douglas J.
Abstract : ABSTRACT: The International Atomic Energy Agency convened a technical meeting on environmental enteric dysfunction (EED) in Vienna (October 28–30, 2015;https://nucleus.iaea.org/HHW/Nutrition/EED_Technical_Meeting/index.html ) to bring together international experts in the fields of EED, nutrition, and stable isotope technologies. Advances in stable isotope–labeling techniques open up new possibilities to improve our understanding of gastrointestinal dysfunction and the role of the microbiota in host health. In the context of EED, little is known about the role gut dysfunction may play in macro- and micronutrient bioavailability and requirements and what the consequences may be for nutritional status and linear growth. Stable isotope labeling techniques have been used to assess intestinal mucosal injury and barrier function, carbohydrate digestion and fermentation, protein-derived amino acid bioavailability and requirements, micronutrient bioavailability and to track microbe-microbe and microbe-host interactions at the single cell level. The noninvasive nature of stable isotope technologies potentially allow for low-hazard, field-deployable tests of gut dysfunction that are applicable across all age groups. The purpose of this review is to assess the state-of-the-art use of stable isotope technologies and to provide a perspective on where these technologies can be exploited to further our understanding of gut dysfunction in EED.